Training Psychological Skills: Efficacy and Assessment of a Nonclinical Psychological Sports Coaching E-Intervention for Young Elite Athletes - Raphaël Bonetti; Fabienne Crettaz von Rotten; Denis Hauw (Current Issues in Sport Science)
Introduction